N‐methyl‐D‐aspartate receptor antibody production from germinal center reactions: Therapeutic implications. Issue 3 (25th March 2018) - Makuch, Mateusz; Wilson, Robert; Al‐Diwani, Adam; Varley, James; Kienzler, Anne‐Kathrin; Taylor, Jennifer; Berretta, Antonio; Fowler, Darren; Lennox, Belinda; Leite, M. Isabel; Waters, Patrick; Irani, Sarosh R
Abstract : Introduction: N‐methyl‐D‐aspartate receptor (NMDAR) antibody encephalitis is mediated by immunoglobulin G (IgG) autoantibodies directed against the NR1 subunit of the NMDAR. Around 20% of patients have an underlying ovarian teratoma, and the condition responds to early immunotherapies and ovarian teratoma removal. However, despite clear therapeutic relevance, mechanisms of NR1‐IgG production and the contribution of germinal center B cells to NR1‐IgG levels are unknown. Methods: Clinical data and longitudinal paired serum NR1‐reactive IgM and IgG levels from 10 patients with NMDAR‐antibody encephalitis were determined. Peripheral blood mononuclear cells from these 10 patients, and two available ovarian teratomas, were stimulated with combinations of immune factors and tested for secretion of total IgG and NR1‐specific antibodies. Results: In addition to disease‐defining NR1‐IgG, serum NR1‐IgM was found in 6 of 10 patients. NR1‐IgM levels were typically highest around disease onset and detected for several months into the disease course. Moreover, circulating patient B cells were differentiated into CD19 + CD27 ++ CD38 ++ antibody‐secreting cells in vitro and, from 90% of patients, secreted NR1‐IgM and NR1‐IgG. Secreted levels of NR1‐IgG correlated with serum NR1‐IgG ( p < 0.0001), and this was observed across the varying disease durations, suggestive of an ongoing process. Furthermore, ovarian teratoma tissue contained infiltrating lymphocytes which produced NR1‐IgG in culture. Interpretation: Serum NR1‐IgM and NR1‐IgG, alongside the consistent production of NR1‐IgG from circulating B cells and from ovarian teratomas suggest that ongoing germinal center reactions may account for the peripheral cell populations which secrete NR1‐IgG. Cells participating in germinal center reactions might be a therapeutic target for the treatment of NMDAR‐antibody encephalitis. Ann Neurol 2018;83:553–561